RULES TO REALITY: ACCOUNTANT’S ADAPTABILITY TO CONTEMPORARY REGULATIONS - Arroza, Guia Elane; Dellava, Jean Margarette; Desquitado, Jeisel Frea; Vasquez, Michael B (President University, 2024)
The ever-evolving setting of accounting regulations presents challenges and opportunities for certified public accountants to adapt and stay ahead in their area of specialization. Ensuring effectiveness in accounting practice and efficiency in the delivery of accounting services as prescribed in the mandated accounting regulations play a crucial role for accountants in their professional practice. Hence, this study was conducted to phenomenologically investigate the accountants’ adaptability to contemporary regulations in the City of Roxas. Specific questions were designed to explore the effect and influence of contemporary regulations on the accountant’s adaptability as well as the challenges faced by accountants in adapting to contemporary regulations. Three accountants were purposively selected using the framework of Creswell on phenomenological research design. A researcher-made semi-structured interview questionnaire duly validated was used to obtain the participant’s perception. The findings revealed three themes: adaptable effect drawn from quality and interaction; adaptable influence stemmed from adaptation and adoption; and, adaptable challenges based on cognition and practice. The study recommends the creation of a program to strengthen the need to adapt to modern regulations especially in the students’ formative years and a training-workshop designed to professors on contemporary regulations and its implications to accounting practice. Future research is further recommended to explore the concepts of adaptability vis-a-vis contemporary regulations in the accounting practice.